Assessing Functioning for Young Children with Neurodevelopmental Conditions: The Development and Testing of a Clinician-Administered Assessment Tool Based on the International Classification of Functioning, Disability and Health Core Sets. - D'Arcy, Emily Francisca (Curtin University, 2023)
This thesis provided an understanding of current assessments of functioning for young children with, or suspected of, neurodevelopmental conditions in Australia, including the evaluation of existing measures. After identifying a need for a comprehensive, valid, and holistic measure of functioning for these children, the ICF Neurodevelopmental Clinician-Administered Assessment of Functioning for young children was developed and evaluated.